1989
DOI: 10.1021/ac00178a011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature gradients on the efficiency of capillary zone electrophoresis separations

Abstract: A flat electrophoretic migration velocity profile Is assumed to be characteristic of current capillary zone electrophoresis (CZE) separations. However, this electrophoretic velocity profile may not actually exist In some experiments due to heat generated within the capillary. The actual migration velocity stream within capillary electrophoresis tubes probably has a parabolic profile. Using a parabolic model, we have developed an expression that quantitatively relates the plate height to experimental parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
175
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(185 citation statements)
references
References 8 publications
(17 reference statements)
9
175
0
Order By: Relevance
“…In 1989, Grushka et al 16 studied the effect of temperature gradients on the efficiency of capillary electrophoresis separations. They reported that Joule heating leads to a temperature-dependent flow velocity, which causes a loss in separation efficiency at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In 1989, Grushka et al 16 studied the effect of temperature gradients on the efficiency of capillary electrophoresis separations. They reported that Joule heating leads to a temperature-dependent flow velocity, which causes a loss in separation efficiency at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] This radial temperature distribution becomes more serious as the diameter of the separation tube increases, even under the same physicochemical conditions. 18 This unevenness can complicate the profile of the electrical conductivity, dynamic viscosity and diffusion coefficient across the electrophoresis channel. 19 The Joule heat in a WE system can be evaluated based on…”
Section: Resultsmentioning
confidence: 99%
“…While microfluidic systems dissipate Joule heating effectively due to favourable surface area to volume ratios, at high electric fields heat generation can raise the temperature and generate temperature gradients in the channel. 43,44 Inclusion of a 30 to 60 s incubation step (E = 0 V cm 21 , no electromigration) during patterning of region (ii) enhanced biotinylated capture protein immobilization in the streptavidin-PA gel at the leading edge of the concentration front. During the incubation period, unbound biotinylated c100p in region (ii) diffused into region (iii), leading to a slow but sharp expansion of the interface according to a competition between reaction and diffusion.…”
Section: The Role Of Da In Control Of Interfaces Between Barcode Regionsmentioning
confidence: 99%